Factorization is an art (3)

Algebra Level 4

( 6 4 x 128 ) 3 + ( 12 8 x 64 ) 3 = ( 12 8 x + 6 4 x 192 ) 3 \large(64^{x}-128)^{3} + (128^{x}-64)^{3} = (128^{x}+64^{x}-192)^{3}

If the sum of all real root(s) of the above equation is a b \dfrac{a}{b} , where a a and b b are coprime positive integers , and a + b = c 2 a+b = c^2 , find c |c| .

Notation : | \cdot | denotes the absolute value function .


The answer is 13.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Tommy Li
Jun 21, 2016

Let p = 6 4 x 128 , q = 12 8 x 64 p=64^{x}-128 , q=128^{x}-64 :

( 6 4 x 128 ) 3 + ( 12 8 x 64 ) 3 = ( 12 8 x + 6 4 x 192 ) 3 (64^{x}-128)^{3} + (128^{x}-64)^{3} = (128^{x}+64^{x}-192)^{3}

p 3 + q 3 = ( p + q ) 3 p^{3}+q^{3} = (p+q)^{3}

p 3 + q 3 = p 3 + 3 p 2 q + 3 p q 2 + q 3 p^{3}+q^{3} = p^{3}+3p^{2}q+3pq^{2}+q^{3}

3 p q ( p + q ) = 0 3pq(p+q)=0

p = 0 \Rightarrow p=0 or q = 0 q=0 or p + q = 0 p+q=0

6 4 x 128 = 0 \Rightarrow 64^{x}-128=0 or 12 8 x 64 = 0 128^{x}-64=0 or 12 8 x + 6 4 x 192 = 0 128^{x}+64^{x}-192=0

2 6 x 2 7 = 0 \Rightarrow 2^{6x}-2^{7}=0 or 2 7 x 2 6 = 0 2^{7x}-2^{6}=0 or 2 6 x ( 2 x + 1 ) = 192 2^{6x}(2^{x}+1)=192

6 x = 7 \Rightarrow 6x=7 or 7 x = 6 7x=6 or 6 x = 6 6x=6

x = 7 6 \Rightarrow x=\frac{7}{6} or x = 6 7 x=\frac{6}{7} or x = 1 x=1

7 6 + 6 7 + 1 = 127 42 \frac{7}{6}+\frac{6}{7}+1=\frac{127}{42}

127 + 42 = 169 = 1 3 2 127+42=169=13^2

12 8 x + 6 4 x 192 = 0 6 4 x ( 2 x + 1 ) = 192 128^{x} + 64^{x} - 192 = 0 \Rightarrow 64^{x}(2^{x} + 1) = 192 \\ not 6 4 x ( 2 + 1 ) = 192 64^{x}(2 +1) = 192

Krutarth Patel - 4 years, 11 months ago

Log in to reply

Ok, I fixed the solution. Thanks you !

Tommy Li - 4 years, 11 months ago

( 6 4 x 128 ) 3 + ( 12 8 x 64 ) 3 = ( 12 8 x + 6 4 x 192 ) 3 , ( 2 6 x 2 7 ) 3 + ( 2 7 x 2 6 ) 3 = { ( 2 6 x 2 7 ) + ( 2 7 x 2 6 ) } 3 3 ( 2 6 x 2 7 ) ( 2 7 x 2 6 ) { ( 2 6 x 2 7 ) + ( 2 7 x 2 6 ) } = 0 2 6 x = 2 7 a n d x = 7 6 . . . . . . . . . . . . 2 7 x = 2 6 a n d x = 6 7 . ( 2 6 x 2 7 ) + ( 2 7 x 2 6 ) = 0 6 4 x ( 2 x + 1 ) = 3 64 , 2 6 x ( 2 x + 1 ) = 3 2 6 . 2 6 x 6 ( 2 x + 1 ) = 3 , 2 6 ( x 1 ) ( 2 x + 1 ) = 3. x = 1. 7 6 + 6 7 + 1 = 85 84 = a b . c = 85 + 84 = 13. \large(64^{x}-128)^3 + (128^{x}-64)^3 = (128^{x}+64^{x}-192)^3,\\ \implies\ \large(2^{6x}-2^7)^3 + (2^{7x}-2^6)^3 =\left \{( 2^{6x}-2^7)+(2^{7x}-2^6)\right \}^3\\ \therefore\ \ 3*(2^{6x}-2^7)*(2^{7x}-2^6)*\{( 2^{6x}-2^7)+(2^{7x}-2^6)\}=0\\ \implies\ \ 2^{6x}=2^7 \ \ \ and\ \ \ x=\frac 7 6.\\ ...........2^{7x}=2^6 \ \ \ and\ \ \ x=\frac 6 7.\\ ( 2^{6x}-2^7)+(2^{7x}-2^6)=0\\ \therefore\ \ 64^x(2^x+1)=3*64,\ \ \implies\ 2^{6x}(2^x+1)=3*2^6.\\ \therefore\ 2^{6x - 6}*(2^x+1)=3,\ \ \implies\ \ 2^{6(x -1)}*(2^x+1)=3.\\ \therefore\ \ x=1.\\ \therefore\ \ \frac7 6+\frac 6 7+1=\frac {85}{84}=\frac a b.\\ \therefore\ \ |c|=\sqrt{85+84}=\Large\ \ \ \color{#D61F06}{13}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...